Komunikasi Humas Pemko Batam dalam Mengatasi Kesimpangsiuran Berita Krisis Pandemi Covid 19 - Siti Rahayu, Juita; Oktavia, Yunisa (STISIPOL Raja Haji, 2023)
The problem is the rapid spread of contamination that can infect humans and can lead to infection. In addition, these infections can be devastating if not treated promptly. Moreover, regardless of the community, the absence of fake information and news can increase the number of victims of the disease. Thus, public authorities are trying to conquer this problem, one of which is through correspondence. With regards to, the motivation behind this. This study is expected to describe the government's local government advertising correspondence methodology in overcoming the chaos over the emergency Covid pandemic news in the city of Batam in 2020, seen from the clear subjective exploration in the Batam City Government Advertising section. Scientists use Middleton's hypothesis in the book Cangara (2017) to discuss PR correspondence techniques. This examination is a kind of subjective exploration that aims to subjectively explain the research strategy. Methods of data collection using interview procedures as the main source of data. The example used in this investigation is the witness from the Batam Regional Government Advertisement. Deliberate Inspection This method is used because it requires tests based on the attributes they have made so that the selected test can provide appropriate data by concentrating on the purpose. While the examination of the data used is an examination of the Miles and Huberman Strategy data starting from data reduction, show of data and reaching a conclusion. The PR from the Batam Regional Government has been great and precise in planning and conducting correspondence methodologies in overcoming the chaos of information about the Covid pandemic emergency in Batam. Batam City Advertisement Public authorities have been successful and very useful in correspondence procedures in Indonesia Beating the chaos over insights about the Covid pandemic emergency in Batam City in 2020.